2017
DOI: 10.1038/s41598-017-13527-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mRNAs encoding CD63 family tetraspanins from the carcinogenic liver fluke Opisthorchis viverrini results in distinct tegument phenotypes

Abstract: The liver fluke Opisthorchis viverrini infects 10 million people in Southeast Asia and causes cholangiocarcinoma (CCA). Fluke secreted and tegumental proteins contribute to the generation of a tumorigenic environment and are targets for drug and vaccine-based control measures. Herein, we identified two tetraspanins belonging to the CD63 family (Ov-TSP-2 and Ov-TSP-3) that are abundantly expressed in the tegument proteome of O. viverrini. Ov-tsp-2 and tsp-3 transcripts were detected in all developmental stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…2). Similar findings have been reported in previous studies on TSP family in other helminth species including adult worms of S. mansoni [33] and O. viverrini [27,42], as well as cuticle dissociation in the free-living nematode C. elegans [46]. The present findings indicate that the TSP Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…2). Similar findings have been reported in previous studies on TSP family in other helminth species including adult worms of S. mansoni [33] and O. viverrini [27,42], as well as cuticle dissociation in the free-living nematode C. elegans [46]. The present findings indicate that the TSP Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Tran et al [33] showed Sm-tsp1 and Sm-tsp2 were highly expressed in cercariae and eggs of S. mansoni, respectively. In Opisthorchis viverrini the highest expression of Ov-tsp-2 and Ov-tsp-3 was observed in the eggs [42]. In contrast, Piratae et al [27] found highly expressed Ov-tsp-1 in the metacercariae of this species.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…TSPs are also found from the proteomic analysis of other helminth EVs (reviewed in [77]). In trematodes, TSPs are involved in tegument development [84-86]. TSP LELs have been tested as vaccine candidates in trematode models of infection [42,47,87] and antibodies produced against TSP vaccine candidates present in S. mansoni and O. viverrini EVs blocked the internalisation of EVs by host cells in both parasites, and decreased pathogenesis in the case of O. viverrine [29,42,88], suggesting a possible mechanism of vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%